Mushroom Cultivation: A Friendly Profession for Rural and Economic Development in Eastern Bihar - Kumar, Santosh; Chand , Gireesh; Erayya,; Kumar, Amarendra; Patel, Deepak Kumar (Indian Journal of Extension Education, 2017)
Mushroom cultivation might be considered as an alternative source of income uplifting the living standards of rural family  and to add good quality protein in their daily diets helping hand in malnutrition abolition. Training was imparted during  the year 2011-12 to 2014-15 by the Department of Plant Pathology, Bihar Agricultural College, (BAU), Sabour, Bihar.  After each training programme data of number of mushroom units established and adoption rate of mushroom cultivation  were collected from the trainees. According to this data 26, 55, 81 and 114 mushroom units were established with adoption  rate, 18.47, 21.73, 28.39 and 23.69 per cent during the year 2011-12, 2012-13, 2013-14 and 2014-15, respectively.  Similarly 26, 34, 50 and 34 per cent rise in the perception level regarding mushroom edibility, mushroom consumption,  mushroom cultivation and profitability was observed in every consecutive year. The data also revealed that 29, 25, 17, 16  and 13 per cent cultivator managed additional income of 6-8, 9-12, 2-5, 12-15 and 16-20 per cent. As far as motive of  farmers before the adoption of the unit are concerned the 25 per cent farmers were of opinion to take loan from Bank,  followed by 23 per cent farmers to take advantage of running government scheme, 21 per cent farmers to meet their future  need and of 13 per cent to become financially independent.
Keywords: Mushroom cultivation; rural development; rural workers; Eastern Bihar